Study of near SOL decay lengths in ASDEX Upgrade under attached and detached divertor conditions. (22nd August 2017) - Sun, H J; Wolfrum, E; Kurzan, B; Eich, T; Lackner, K; Scarabosio, A; Pérez, I Paradela; Kardaun, O; Faitsch, M; Potzel, S; Stroth, U
Abstract: A database with attached, partially detached and completely detached divertors has been constructed in ASDEX Upgrade discharges in both H-mode and L-mode plasmas with Thomson Scattering data suitable for the analysis of the upstream SOL electron profiles. By comparing upstream temperature decay width, λ T e, u, with the scaling of the SOL power decay width, λ q ∥ e, based on the downstream IR measurements, it is found that a simple relation based on classical electron conduction can relate λ T e, u and λ q ∥ e well. The combined dataset can be described by both a single scaling and a separate scaling for H-modes and L-modes. For the single scaling, a strong inverse dependence of, λ T e, u on the separatrix temperature, T e, u, is found, suggesting the classical parallel Spitzer–Harm conductivity as dominant mechanism controlling the SOL width in both L-mode and H-mode over a large set of plasma parameters. This dependence on T e, u explains why, for the same global plasma parameters, λ q ∥ e in L-mode is approximately twice that in H-mode and under detached conditions, the SOL upstream electron profile broadens when the density reaches a critical value. Comparing the derived scaling from experimental data with power balance, gives the cross-field thermal diffusivity as χ ⊥ ∝ T e 1/2 / n e, consistent with earlier studies on Compass-D, JET and Alcator C-Mod. However, the possibility of the separate scalings for different regimes cannot be excluded, which gives results similar to those previously reported for the H-mode, but here the wider SOL width for L-mode plasmas is explained simply by the larger premultiplying coefficient. The relative merits of the two scalings in representing the data and their theoretical implications are discussed.